Literature Review: Application of Computer Integrated Manufacturing (CIM) to Increase Operational Effectiveness and Company Productivity - Hadi Amin, Ahsanul; Sukma Saputri, Yunita (Information Technology International Journal, 2023)
Computer Integrated Manufacturing(CIM) is a manufacturing method and the name of an automated computer system by which the individual engineering, production, marketing, and support functions of a manufacturing company are organized. In a CIM system, functional areas such as design, analysis, planning, purchasing, cost accounting, inventory control, and distribution are linked via computers providing direct control and monitoring of all process operations. This study aims to analyze and review the literature on Computer Integrated Manufacturing in previous research through references to international journal articles by considering the discussion of the application of CIM in a manufacturing industry case for production efficiency and company operations with article sampling parameters such as being indexed in Scopus Q3.